Capillary zone and agarose plasma protein electrophoresis in the sand tiger shark (Carcharias taurus) - Cray, Carolyn; Soto, Jeny; Hyatt, Michael W.; Christiansen, Emily F.; Lyons, Kady; Wyffels, Jennifer T. (Frontiers in Veterinary Science, 2025)
Protein electrophoresis is a tool used in the health assessments of non-mammalian vertebrates. In elasmobranchs, agarose gel electrophoresis (AGE) has been described in various species and a newer method called capillary zone electrophoresis (CZE) has been developed and implemented in the undulate skate (Raja undulata) and nursehound shark (Scyliorhinus stellaris). The study goals were to implement AGE and CZE methods on plasma samples from the sand tiger shark (Carcharias taurus) and examine differences in resolution as well as to calculate reference intervals (RI). Plasma was obtained from aquarium sharks (n = 23) and free-ranging sharks (n = 62) sampled during field research conducted from 2017 to 2023. As with previous reports, CZE was found to provide superior resolution with definition of two major globulin migrating fractions compared to AGE. Overall, the alpha and beta migrating fractions were well correlated between the methods (r = 0.92, 0.89, respectively, p < 0.0001). The correlation for the gamma fraction was weaker (r = 0.42, p = 0.002) as the CZE fraction was lower in concentration versus AGE. There were minor, but significant, differences between the concentration of some of the fractions in samples from sharks under managed care versus free-ranging animals which necessitated the production of two sets of RI. In total, this information may help in further studies to address the applicability of these tools in the management of this species under human care as well as in health assessments of free-ranging sharks.